The Implementation of South Sumatera Industrial Downstreaming for Rubber Products Strategic Policy with The Establishment of Tanjung Api-Api Special Economic Zone - Aisyah, Sari Mutiara; Yusa, M. Yustian; Supli, Nur Aslamiah; Ikhsan, OK.Mohammad Fajar (Universitas Muhammadiyah Yogyakarta, 2021)
The downstreaming option to provide added value to local industries, especially developing countries in the Global Value Chain (GVC) era as a way to increase competitiveness and seizing global markets, is inevitable. This paper focus on the analysis of the developments and limitations faced in the implementation of the Strategic Policy of South Sumatra Rubber Product Downstreaming with the establishment of Tanjung Api-Api Special Economic Zone. At the regional level, the idea of developing SEZ (Special Economic Zone) aims to prepare investment institutions in improving the investment climate in Southeast Asia region and manifesting ASEAN as a single market and production base as a component of the 2015 ASEAN Economic Community. This study used an exploratory and descriptive qualitative research method, where the depth and context of the data are important. Data from this study consisted of secondary data through literature study and analysis of documents and primary data obtained from interview as well as through field research. The author concludes that the industrial downstreaming of rubber products in South Sumatra has not been maximally carried out, it was still segmented, it was not conducted linearly, both production and coordination between the central government and the locals. Tanjung Api-Api SEZ as a hub for international trade and industrialization of rubber commodities also encountered various obstacles including infrastructure (deep sea port) at this point was inadequate, certainty of fiscal incentives for companies relocating to SEZ and licensing.